2003
DOI: 10.1002/ijc.11331
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK signaling diminishes early but not late cellular stress‐induced apoptosis

Abstract: The human leukemic T-cell line Jurkat was used to define the role of the cellular stress pathway with its key player kinase JNK in cancer therapy-induced apoptosis. JNK activity was inhibited by stable transfection with a dominant negative mutant of the upstream kinase JNKK/MKK4 or with the novel, potent and selective JNK1, -2 and -3 inhibitor SP600125. Inhibition of JNK activity delayed the onset of apoptosis induced by cisplatin, doxorubicin, ␥-irradiation and CD95-L but did not prevent apoptosis per se. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
(65 reference statements)
3
15
1
Order By: Relevance
“…Indeed, we found that doxorubicin-induced down-regulation of Mcl-1 levels is mediated via JNK and that ColI inhibited doxorubicin-induced JNK activation. Our results showed that JNK is important for doxorubicin-induced caspase activation and apoptosis in T-ALL cells, which is in line with previous studies (29,33). In addition, JNK has also been involved in the degradation of Mcl-1 through its phosphorylation and ubiquitination, a pathway that has recently been shown to play a key role in the sensitization of breast cancer cells to TRAIL by antimicrotubules agents (47) and in the synergy between the Bcl-2 pan-inhibitor ABT-737 and retinamide in the apoptosis of lymphoblastic leukemia cells (48).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, we found that doxorubicin-induced down-regulation of Mcl-1 levels is mediated via JNK and that ColI inhibited doxorubicin-induced JNK activation. Our results showed that JNK is important for doxorubicin-induced caspase activation and apoptosis in T-ALL cells, which is in line with previous studies (29,33). In addition, JNK has also been involved in the degradation of Mcl-1 through its phosphorylation and ubiquitination, a pathway that has recently been shown to play a key role in the sensitization of breast cancer cells to TRAIL by antimicrotubules agents (47) and in the synergy between the Bcl-2 pan-inhibitor ABT-737 and retinamide in the apoptosis of lymphoblastic leukemia cells (48).…”
Section: Discussionsupporting
confidence: 93%
“…ColI Inhibits Doxorubicin-induced JNK Activation-Previous studies have shown that JNK is involved in doxorubicin-induced apoptosis of T-ALL cells (29,33) and that Mcl-1 stability and levels can be regulated by JNK (34). Thus, we considered the possibility that doxorubicin reduces Mcl-1 levels through a mechanism involving JNK, and that ColI could restore Mcl-1 levels by blocking JNK activation.…”
Section: Volume 287 • Number 21 • May 18 2012mentioning
confidence: 99%
“…Moreover, Debatin et al have shown that inhibition of JNK activity delays the onset of apoptosis induced by cellular stress (including cisplatin and doxorubicin) in a Jurkat T cell model. 40 Therefore, we propose, on the basis of the current data as well as recent data obtained in other model systems, that LMP1 may potentiate caspase activation and mitochondrial damage through its CTAR2 domain, potentially via JNK-dependent pathways (Fig. 5d).…”
Section: Discussionsupporting
confidence: 71%
“…Recently, the JNK inhibitor has been shown to inhibit chemotherapyinduced apoptosis, at least in part, through the inhibition of caspase-3 activity (31). In this study, this small molecule inhibitor of JNK inhibits significantly the apoptotic cell killing induced by Wnt-1 siRNA, anti-Wnt-1 monoclonal antibody, or Dvl siRNA (Fig.…”
Section: Resultsmentioning
confidence: 58%